2015
DOI: 10.1177/2042018815571892
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormonal status among children with obesity

Abstract: Background: It is presumed that free T4 and thyroid-stimulating hormone (TSH) levels are related to obesity, but the findings are inconsistent. In this study we evaluated T4 and TSH concentrations between normal children and those with obesity and possible correlations between body mass index (BMI) and these markers. Methods: In this prospective study, 190 children who were overweight and obese and 133 children without obesity of the same age and sex were evaluated. Thyroid function tests (TSH, total T4, free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 29 publications
7
33
1
5
Order By: Relevance
“…A recently published study by Ghergherehchi and Hazhir [61] also concludes that TSH levels were significantly higher in obese children compared with the control group (14.7% vs. 6.8%), but in contrast with the earlier mentioned studies, they found that total T4 was also significantly higher in children with obesity (9.5% vs. 3.8% in controls). Among children with obesity…”
Section: Thyroid Function In Overweight and Obese Childrenmentioning
confidence: 82%
See 3 more Smart Citations
“…A recently published study by Ghergherehchi and Hazhir [61] also concludes that TSH levels were significantly higher in obese children compared with the control group (14.7% vs. 6.8%), but in contrast with the earlier mentioned studies, they found that total T4 was also significantly higher in children with obesity (9.5% vs. 3.8% in controls). Among children with obesity…”
Section: Thyroid Function In Overweight and Obese Childrenmentioning
confidence: 82%
“…The authors also found a significantly positive correlation between TSH and T4 level and BMI z-score, but the correlations between fT3 and fT4 and BMI z-score were not significant [61].…”
Section: Prace Poglądowementioning
confidence: 89%
See 2 more Smart Citations
“…TSH serum levels correlate positively with BMI in adults as well as in children, while SH is more frequent in obese subjects compared to non-obese subjects [15,16]. In obese subjects, TSH values consistent with mild SH may revert to normal after weight loss [17,18].…”
Section: General Medical Conditionsmentioning
confidence: 90%